An efficient and stable method for short maturity Asian options. Issue 12 (27th July 2018) - Chatterjee, Rupak; Cui, Zhenyu; Fan, Jiacheng; Liu, Mingzhe
Abstract : In this paper, we develop a Markov chain‐based approximation method to price arithmetic Asian options for short maturities under the case of geometric Brownian motion. It has the advantage of being a closed‐form approximation involving only matrices. It is an accurate, efficient, and stable method for the pricing and hedging of short maturity arithmetic Asian options for which previous methods in the literature have shown either slower convergence or instabilities in hedging parameters. We demonstrate that this method is as good as and sometimes better than existing approximation methods in the literature.